TANTANGAN GURU MENGIMPLEMENTASIKAN PEMBELAJARAN BERBASIS TEKNOLOGI DIGITAL DALAM KURIKULUM MERDEKA DI UPT SDN 023 PANDAU JAYA - Agnes Afrillia; Febrina Dafit (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to identify the challenges faced by teachers in implementing digital technology-based learning within the Merdeka Curriculum at UPT SDN 023 Pandau Jaya. The research employed a qualitative case study approach with data collected through observations, interviews, and documentation. The informants consisted of homeroom teachers of classes VA and VB, as well as students from the same classes. The findings indicate four main challenges in implementing digital technology-based learning. In terms of teacher competence, differences were found in teachers’ abilities to operate digital devices and apply TPACK, resulting in uneven utilization of technology. Regarding infrastructure, ICT facilities are available but not optimally used due to limited devices and technical issues. In the aspect of school support, regular training and guidance from the principal have been provided, yet some teachers still require additional assistance. From a cultural perspective, varying levels of adaptability between younger and senior teachers influence the smooth integration of technology, although all teachers demonstrate positive attitudes and willingness to learn. This study emphasizes that teacher competence, facilities, institutional support, and school culture play crucial roles in the successful implementation of digital technology-based learning in accordance with the Merdeka Curriculum.